‘We all have the same goals’? Goal diversity in cross-sector collaborations of cultural education - Arnold, Marie-Therese; Kolleck, Nina (Frontiers in Education, 2025)
Following the current rise of cross-sector networks in education, we take a closer look at the supply side in the field of cultural education in Germany. We consider goal diversity in cross-sector collaborations and aim to provide insights into the group-specific goals of actors in the initial phase of collaborations. Using the lens of collaborative governance, collaborative engagement, and goal diversity research, we conducted 24 semi-structured interviews which we analyzed using thematic qualitative content analysis. We identified distinct goals for each of the five participating groups. These goals can be assigned to the macro, meso, and micro levels of the network, providing information about the direction of the goals and emphasizing the dynamic interplay of goals and their implications for collaborative dynamics. Future research could determine whether the results can be found in other contexts.